2009
DOI: 10.1016/j.ntt.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cocaine exposure alters emotional arousal regulation and its effects on working memory

Abstract: While prenatal cocaine exposure (PCE) has been associated with arousal dysregulation and attentional impairments in both human and animal studies, the neurobiological bases of these teratogenic effects have not been well characterized. In the current study, we report functional neuroimaging observations of these effects in exposed youth. Using functional magnetic resonance imaging (fMRI), we embedded task-irrelevant emotional distracters in a working memory task to examine the interaction of emotional arousal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 63 publications
10
84
3
Order By: Relevance
“…We found a significant association between PCE and short-term memory (Richardson et al, 2009), and other researchers have reported deficits in specific areas such as verbal reasoning/memory (Bennett et al, 2002), executive function , cognitive processing/learning (Bridgett et al, 2011;Mayes et al, 2005Mayes et al, , 2007, visual spatial/math skills (Singer et al, , 2008, visual motor integration Schroder et al, 2004), and attention, inhibitory control, and impulsivity (Accornero et al, 2007;Bandstra et al, 2001;Bendersky et al, 2003;Carmody et al, 2011;Noland et al, 2005;Rose-Jacobs et al, 2009). However, there are also reports that show no negative effects of PCE on specific areas of cognition (Betancourt et al, 2011;Eyler et al, 2009;Hurt et al, 2009;Li et al, 2009;, and most groups, including ours, do not find a relation between PCE and global cognitive development (Accornero et al, 2007;Bandstra et al, 2002;Frank et al, 2005;Hurt et al, 1997Hurt et al, , 2001Messinger et al, 2004;Morrow et al, 2004Morrow et al, , 2006Singer et al, 2004).…”
Section: Introductioncontrasting
confidence: 46%
See 1 more Smart Citation
“…We found a significant association between PCE and short-term memory (Richardson et al, 2009), and other researchers have reported deficits in specific areas such as verbal reasoning/memory (Bennett et al, 2002), executive function , cognitive processing/learning (Bridgett et al, 2011;Mayes et al, 2005Mayes et al, , 2007, visual spatial/math skills (Singer et al, , 2008, visual motor integration Schroder et al, 2004), and attention, inhibitory control, and impulsivity (Accornero et al, 2007;Bandstra et al, 2001;Bendersky et al, 2003;Carmody et al, 2011;Noland et al, 2005;Rose-Jacobs et al, 2009). However, there are also reports that show no negative effects of PCE on specific areas of cognition (Betancourt et al, 2011;Eyler et al, 2009;Hurt et al, 2009;Li et al, 2009;, and most groups, including ours, do not find a relation between PCE and global cognitive development (Accornero et al, 2007;Bandstra et al, 2002;Frank et al, 2005;Hurt et al, 1997Hurt et al, , 2001Messinger et al, 2004;Morrow et al, 2004Morrow et al, , 2006Singer et al, 2004).…”
Section: Introductioncontrasting
confidence: 46%
“…These adolescent outcomes were not found to be affected by PCE in other reports (Betancourt et al, 2011;Li et al, 2009;Rose-Jacobs et al, 2011). However, there are few reports in the literature, so this association remains to be determined.…”
Section: Discussionmentioning
confidence: 49%
“…Sixteen studies from 7 cohorts defined cocaine exposure dichotomously: "exposed" versus "nonexposed" 18,23,24,[32][33][34][35][36][37][38][39][40][41][42][43] or "heavy/persistent" versus "some/ none." 21 Six studies from 1 cohort defined "heavy" as first trimester use $3 times per week.…”
Section: Definition Of Pcementioning
confidence: 99%
“…24,33,[38][39][40][41][42]47 All had small sample sizes (N = 34-56), used few covariates other than other prenatal drug exposures, and had different neuroimaging methods (3 used similar methods).…”
Section: Neuroimagingmentioning
confidence: 99%
“…The aforementioned deficits in arousal regulation associated with prenatal cocaine exposure appear to underlie brain and behavior-related working memory function. Li et al [139] showed differential patterns of activation as a function of emotionmemory interactions. Increased demands on memory load diminished emotion-related activation in the amygdala in controls but not in the exposed group.…”
Section: Working Memorymentioning
confidence: 99%